2002
DOI: 10.1523/jneurosci.22-01-00062.2002
|View full text |Cite
|
Sign up to set email alerts
|

Glutamine Uptake by Neurons: Interaction of Protons with System A Transporters

Abstract: Astrocytes provide the glutamine required by neurons to synthesize glutamate and GABA. However, the mechanisms involved in glutamine transfer from glia to neurons have remained poorly understood. Recent work has implicated the System N transporter SN1 in the efflux of glutamine from astrocytes and the very closely related System A transporters SA1 and SA2 in glutamine uptake by neurons. To understand how these closely related proteins mediate flux in different directions, we have examined their ionic coupling.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
185
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 190 publications
(202 citation statements)
references
References 33 publications
14
185
1
Order By: Relevance
“…Consistently, our data indicated that proliferation of MDA-MB-231(SA) cells in serine-free conditions was strongly inhibited by PSAT1 knockdown. Serine is transported in and out of cells via amino acid transporters: the Na+-dependent transporters ASCT1 (SLC1A4) and ASCT2 (SLC1A5) [21,22], the system A transporters SA1 (SLC38A1) and SA2 (SLC38A2) [23] and the Na+-independent alanineserine-cysteine transporter 1 (Asc-1 (SLC7A10)) [24]. One of these transporters, In addition to cell proliferation, our data suggest that enhanced serine biosynthesis may promote other aspects in the metastatic cascade.…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, our data indicated that proliferation of MDA-MB-231(SA) cells in serine-free conditions was strongly inhibited by PSAT1 knockdown. Serine is transported in and out of cells via amino acid transporters: the Na+-dependent transporters ASCT1 (SLC1A4) and ASCT2 (SLC1A5) [21,22], the system A transporters SA1 (SLC38A1) and SA2 (SLC38A2) [23] and the Na+-independent alanineserine-cysteine transporter 1 (Asc-1 (SLC7A10)) [24]. One of these transporters, In addition to cell proliferation, our data suggest that enhanced serine biosynthesis may promote other aspects in the metastatic cascade.…”
Section: Discussionmentioning
confidence: 99%
“…[42][43][44][45] Very recently, Ju et al 46) demonstrated that protonation/deprotonation of two histidine residues on the extracellular domain regulated glycine transport activity via one isoform of glycine transporters (GLYT1), which are members of the Na ϩ /Cl Ϫ -dependent neurotransmitter transporter family. Furthermore, they showed that zinc noncompetitively inhibits the glycine transport activity with its chelating with two histidine residues, of which one is overlapped with proton binding sites.…”
Section: Discussionmentioning
confidence: 99%
“…These system N amino acid transporters mediate the uptake of 1 glutamine molecule with the net uptake of 1 Na + in exchange of a proton. The other members of the SLC38 family, the system A transporters (SNAT1, SNAT2, SNAT4) are not able for countertransport of protons [13][14][15][16]. SNAT3 is highly abundant in liver, kidney, and brain, and expression has also been reported for adipose tissue, pancreas, skeletal muscle, and eye.…”
Section: Introductionmentioning
confidence: 99%